Rodzina jako wspólnota na przykładzie potrydenckiej społeczności zakonnej norbertanek zwierzynieckich w Krakowie - Kaczor-Scheitler, Katarzyna (Bibliotekarz Podlaski Ogólnopolskie Naukowe Pismo Bibliotekoznawcze i Bibliologiczne, 2023)
The subject of the article is to present the post-Tridentine community of the Norbertine nuns of Zwierzyniec in Cracow, characterized by a spiritual bond based on common values, beliefs, ideals, and goals. It is argued that the internal life of this community was determined by rules and constitutions, defining tasks and areas of specific activity, adapted to the requirements in force after the Council of Trent. Attention is focused on intra-Community relations expressed in the commonly used “family” nomenclature (prioress, subprioress, circus worker, librarian, sacristan, cellarer, vestiress, guest sister, doorkeeper, mother, spiritual daughter), presented in the manuscript Acts of the splendid Premonstratensian order… The community of Norbertine nuns in Zwierzyniec was based on a spiritual bond, responsibility for each other, duties that were religiously motivated, modeled on the family, and built on the basis of sisterly love and obedience. The reflection also covered the handwritten meditations of Norbertine nuns and printed ascetic and mystical writings from the 17th century, stored in the archives of Zwierzyniec, testifying to the religious fervor of the artists and the need for collective prayer effort of the community.
Keywords: zwierzyniec

Conservation of the Late Romanesque Sandstone Portal of the Church of the Premonstratensian Convent in Kraków, Poland - Pachuta, Karolina; Bojęś-Białasik, Anna; Łyczak, Monika; Bromowicz, Jan; Wedekind, Wanja; Szyma, Marcin; Czechowicz, Jacek (International Journal of Conservation Science, 2022)
The church of the Premonstratensian Convent in Kraków is an early brick structure with stone detail, dating to the mid-13th century. One of the most precious elements preserved of the original church is the monumental late-Romanesque portal made of sandstone. In the wake of the accrual of cultural layers outside the church in the following centuries, what used to be the main portal leading into the church found itself sunk in the ground up to half of its height. Additionally, the portal was covered by a baroque tower in the 17th century. That had a highly negative impact on the condition of the portal which currently urgently required undertaking interdisciplinary research and conservation works. The archaeological digs made it possible to uncover the complete portal, while the research aimed at defining the reasons and degree of damage to the stone. The research consisted in petrographic examinations, examination of the structure of decay caused by dampness and salt, and electric conductivity tests of the sandstone. The conclusions from the research provided the foundation for designing and implementing a conservation works strategy to save, preserve, and show this exceptional work to the public.
Keywords: zwierzyniec

Die Handschrift rkps 67 des Prämonstratenserinnenstifts Zwierzyniec bei Krakau: Sicherung und Organisation konstitutiven Wissens - Kornemann, Ivonne (Von der Ostsee zum Mittelmeer: Forschungen zur mittelalterlichen Geschichte für Wolfgang Huschner, 2019)
Keywords: zwierzyniec

Krzyż i chwała : błogosławiona Bronisława i Konwent Panien Norbertanek na Zwierzyńcu w Krakowie = The cross and glory : blessed Bronislava and Norbertine Canonesses Convent in Zwierzyniec, Cracow - Stefaniak, Piotr (Księgarnia św. Jacka, 2019)
Keywords: zwierzyniec; 👤 bronislava of kamień

Problem genezy formalnej prezbiterium w krakowskim kościele Norbertanek na Zwierzyńcu - Cierpisz, Szymon (Rocznik krakowski Towarzystwo Miłośników Historii i Zabytków Krakowa, 2018)
Keywords: zwierzyniec

Late Romanesque Convent Church of the Norbetine Sisters in Zwierzyniec in Cracow in the Light of Architectural Research from 2010-2011 - Bojes-Bialasik, Anna; Czechowicz, Jacek (Cihla a stavební keramika ve stredoveku a novoveku v mestské architekture strední Evropy, 2015)
Keywords: zwierzyniec

Manuscript Work of the Zwierzyniec Norbertine Nuns of the Seventeenth and Eighteenth Century - Kaczor-Scheitler, Katarzyna (Analecta Praemonstratensia, 2014)
Keywords: zwierzyniec

Inwentarz dóbr konwentu zwierzynieckiego w roku Pańskim 1722 spisany - Kazusek, Szymon (Nasza Przeszłość, 2013)
The subject of this publication is the only remaining early-modern inventory of the estates of the convent of Premonstratensians at Zwierzyniec near Cracow. This manuscript contains the description of the real estates in twenty villages being in the property of the Zwierzyniec convention in 1722. The inventory is an excellent source for the research on the farm economy in convent estate. The names of convent villages which the described real estates come from have in huge majority endured until contemporary times. At present some places are within the administrative borders of Cracow, Krzeszowice or Będzin, other exist under previous or modified names, whereas one of the described villages (Zakościele) has not remained until present times. Analysing the content of the inventory it is possible to obtain detailed information about the size, the state and the organisation of the buildings that were convent property, as well as about the leases and their financial aspects. The image emerging after studying the inventory shows a wide diversity of technical condition of farm buildings. What is more, the presented description includes information about buildings in very bad state as well as about renovated or new ones.
Keywords: zwierzyniec

Pilger und Stifter. Zu den Sakralstiftungen und zur Herkunft des Fürsten Jaxa - Rajman, Jerzy (Monarchische und adlige Sakralstiftungen im mittelalterlichen Polen, 2012)
Keywords: zwierzyniec

Nowożytne relacje o początkach klasztoru na Zwierzyńcu - Rajman, Jerzy (Res Gestae, 2007)
Keywords: zwierzyniec